Analysis of crane track degradation due to operation. (January 2016) - Kulka, Jozef; Mantic, Martin; Fedorko, Gabriel; Molnar, Vieroslav
Abstract: This paper describes a professional verification of crane track beams, determination of residual durability of selected beams and suggestion of necessary measures with regard to possibility of future operation of the whole crane track. The most seriously loaded beams in one of metallurgical plants were analysed. In this paper the problems of crane track damage due to operation are analysed. Data for the analysis were obtained by the experimental measurements by means of strain-gauge measurement of track loading and a device operator provided the collected data about the annual amounts of manipulated material. Based on these data it is possible to determine, by means of one of the applied theories, the residual life of examined construction. Highlights: Computer simulation of crane track operational loading Strain-gauge measuring of stress increments Evaluation of maximum amplitude and number of damaging cycles Determination of fatigue damage for the individual beams of crane track